Selection Dynamics, Asymptotic Stability, and Adaptive Behavior - Van Huyck, John B.; Cook, Joseph P.; Battalio, Raymond C. (Journal of Political Economy, 1994)
Selection dynamics are often used to distinguish stable and unstable equilibria. This is particularly useful when multiple equilibria prevent a priori comparative static analysis. This paper reports an experiment designed to compare the accuracy of the myopic best-response dynamic and an inertial selection dynamic. The inertial selection dynamic makes more accurate predictions about the observed mutual best-response outcomes.